Crime prevention volunteering in Japan: Japanese citizens' contribution to low crime rates - Herber, Erik (International journal of law, crime and justice, 2018)
Japanese crime rates are, and have been for decades, among the lowest in the industrialized world (Ministry of Justice, 1964-2016). Be that as it may, in the past 10 years the number of volunteers involved in crime prevention has risen from around 200.000 to almost 3.000.000 (National Police Agency, 2016). Many of these volunteers accompany children going to school; others regularly “inspect dangerous places.” The most popular activity, however, is that of patrolling the neighborhood (National Police Agency,2016). These volunteers’activities come on top of growing numbers of volunteers involved in helping ex-convicts and juveniledelinquents reintegrate into society. This is a remarkable development not only in view of its unparalleled scale but also in view of thefact that in Japan, like in many other industrialized countries,“public demand” has in recent years lead to harsher sentences for criminals, and more public attention to the needs of victims rather than criminals.